2012
DOI: 10.1371/journal.pone.0045099
|View full text |Cite
|
Sign up to set email alerts
|

A Lentiviral Gene Therapy Strategy for the In Vitro Production of Feline Erythropoietin

Abstract: Nonregenerative anemia due to chronic renal failure is a common problem in domestic cats. Unfortunately, administration of recombinant human erythropoietin often only improves anemia temporarily due to antibody development. In this in vitro study, feline erythropoietin cDNA was cloned from feline renal tissue and utilized in the construction of a replication-defective lentiviral vector. The native recombinant feline erythropoietin (rfEPO) sequence was confirmed by sequencing. Upon viral vector infection of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This study builds on previous results demonstrating the effectiveness of a replication-defective lentiviral gene therapy vector as a method of efficiently delivering the feEPO gene in vitro. 29 The Vector D lentivirus features the constitutively active SV40 promoter, which is functionally attenuated relative to the CMV promoter. Prior studies 35 have shown more stable, long-term transgene expression with the SV40 promoter relative to with the CMV promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study builds on previous results demonstrating the effectiveness of a replication-defective lentiviral gene therapy vector as a method of efficiently delivering the feEPO gene in vitro. 29 The Vector D lentivirus features the constitutively active SV40 promoter, which is functionally attenuated relative to the CMV promoter. Prior studies 35 have shown more stable, long-term transgene expression with the SV40 promoter relative to with the CMV promoter.…”
Section: Discussionmentioning
confidence: 99%
“…feEPO mRNA was previously PCR amplified from feline renal tissue-derived RNA, and the resulting reverse-transcribed cDNA was incorporated into an initial lentiviral vector system, referred to here as Vector A. 29 The feEPO gene (cDNA) was subsequently utilized in the design and construction of a novel third-generation, replication-defective lentiviral vector, referred to here as Vector D. A UC Davis Biological Use Authorization (BUA; #895) was approved for the use of this vector. The plasmidencoded feEPO cDNA was confirmed by sequencing (GenBank JQ413414).…”
Section: Design and Packaging Of Lentiviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation